Stress With Parents and Peers: How Adolescents From Six Nations Cope With Relationship Stress. (14th February 2013) - Seiffge‐Krenke, Inge; Persike, Malte; Karaman, Neslihan Güney; Cok, Figen; Herrera, Dora; Rohail, Iffat; Macek, Petr; Hyeyoun, Han
<x xml:space="preserve">Abstract</x> This study investigated how 2000 adolescents from middle‐class families in six countries perceived and coped with parent‐related and peer‐related stress. Adolescents from Costa Rica, Korea, and Turkey perceived parent‐related stress to be greater than peer‐related stress, whereas stress levels in both relationship types were similar in the Czech Republic, Germany, and Pakistan. Female adolescents predominantly reported higher levels of peer‐related stress than male adolescents. Adolescents in all countries used negotiating and support‐seeking to cope with relationship stress more often than emotional outlet or withdrawal. Withdrawal occurred more often to deal with parent‐related than with peer‐related stress. Results suggest that adolescents across countries competently coped with relationship stress. However, patterns of what adolescents perceived as stressful and how they coped varied between countries.